Assessing the Effects of Real Exchange Rate Depreciation on the Moroccan Economy: Evidence based on SVAR Approach with Sign Restrictions - AZZOUZI, Asmae; BOUSSELHAMI, Ahmed (Theoretical and Practical Research in Economic Fields; Vol 12 No 2 (2021): TPREF, Volume XII, Issue 2(24), Winter 2021, 2021)
The purpose of this paper is to analyze the dynamic response of a small subset of variables to exchange rate shocks by using a new method based on a set of theory-consistent sign restrictions for the purpose of identifying shocks over time (1995Q1–2019Q1) in the Moroccan economy. It is important to note that the current account presents the so-called “J-curve” phenomenon. Additionally, Morocco entered into a period of deeper and longer recession and higher inflation following the dirham’s depreciation. Following a real depreciation, the output has little effect on improving the current account balance. Our results suggest that the monetary authorities reacted immediately to exchange rate shocks by raising their interest rates to prevent the economy from falling into deflation.